2021
DOI: 10.3390/molecules26134015
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific Positioning of Palmitic Acid in Triacylglycerol Structure of Enzymatically Modified Lipids Affects Physicochemical and In Vitro Digestion Properties

Abstract: Tripalmitin-(PPP, 81.2%), 1,3-dipalmitoyl-2-oleoylglycerol-(POP, 64.4%), 1,2-dipalmitoyl-3-oleoylglycerol-(PPO, 86.5%), and 1,3-dioleoyl-2-palmitoylglycerol-(OPO, 50.2%)-rich lipids with different regiospecific positions of palmitic acid (P) were synthesized via acetone fractionation and lipase-catalyzed acidolysis, and their physicochemical and hydrolytic characteristics were compared. Triacylglycerols (TAGs) with higher content of P, wherein P was at the sn-1 (or 3) position, had higher melting points, cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The release of FFAs from all emulsions during the first 10 min was very fast. In the simulated small intestine stage, the lipids in the emulsion were emulsified by bile acids, and then fatty acids in the sn ‐1, 3 position of triglyceride (TAG) were hydrolyzed by small intestine lipase 45 . Within the initial 10 min, most lipases would quickly bind to the sn ‐1, 3 position of TAG in the emulsions, resulting in a maximum of enzyme–substrate bonding and rapid FFA production 46 .…”
Section: Resultsmentioning
confidence: 99%
“…The release of FFAs from all emulsions during the first 10 min was very fast. In the simulated small intestine stage, the lipids in the emulsion were emulsified by bile acids, and then fatty acids in the sn ‐1, 3 position of triglyceride (TAG) were hydrolyzed by small intestine lipase 45 . Within the initial 10 min, most lipases would quickly bind to the sn ‐1, 3 position of TAG in the emulsions, resulting in a maximum of enzyme–substrate bonding and rapid FFA production 46 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the incorporated FAs at the sn -1,3 position of OSO-rich fat were almost completely hydrolyzed by in vitro digestion for 120 min. The authors previously showed that OPO-rich lipid was more easily digested than PPO-rich lipid, as the amounts of FFAs (%) released from each at 30, 60, and 120 min were 88.6%, 91.35%, and 104.9%, and 64.9%, 69.7%, and 75.7%, respectively, during the same in vitro multi-step digestion [ 21 ]. Therefore, the in vitro digestibility of lipids was affected by the type of FAs incorporated at the sn -1,3 position of TAG, and the digestibility was increased by less saturation and FAs with shorter carbon chains in the following descending order of OPO- > PPO- > OSO- > SSO-rich fats.…”
Section: Resultsmentioning
confidence: 99%
“…SSO-rich and OSO-rich fats were synthesized from FHSBO (SSS-rich fat) and oleic acid rich fatty acids by lipase-catalyzed acidolysis followed by acetone fractionation, as presented in Figure 7 [ 21 ]. The completely dissolved FHSBO was mixed with oleic acid (1:2 molar ratio) in an Erlenmeyer flask (500 mL) with screw cap.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cow milk and vegetable oils generally contain SFAs esterified to the sn-1 and sn-3 positions and USFAs at sn-2 position. These differences not only affect the nutrition and digestion of fats, but also cause stool hardness and constipation due to the preferential hydrolysis of PA in the sn-1,3 positions by pancreatic lipase to form calcium soap which is water-insoluble and can hardly be absorbed in the intestine of babies (Lee and Chang, 2021). In contrast, when PA is esterified to the sn-2 position, the 2-monoacylglycerol formed is readily absorbed (Ghide and Yan, 2021), therefore, the kinetics of hydrolysis of different TAGs may induce a different digestive process.…”
Section: Introductionmentioning
confidence: 99%